Analisis Perbedaan Tingkat Kebangkrutan Menggunakan Metode Altman Z-Score dan S-Score Springate pada Perusahaan Pariwisata Sebelum dan Selama Pandemi Covid-19 - Hanifah Mansyurah; Mayar Afriyenti (Jurnal Eksplorasi Akuntansi, 2023)
The purpose of this study is to determine the difference in bankruptcy rates in tourism companies before and during the Covid-19 pandemic.The results showed that there were different results in predicting bankruptcy before and after the pandemic. The results of this study indicate the potential for financial distress using Altman's Z"-Score method that in 2018 there were 11 companies experiencing financial distress, 2 companies in the gray area, and 2 non-financial distress companies. In 2019 there were 10 companies experiencing financial distress, 3 companies in the gray area, and 2 non-financial distress companies. In 2020 there are 8 companies experiencing8 companies experiencing the gray area and 4 non-financial distress companies. In 2021 there are 10 companies experiencing financial distress, 1 company in the gray area, and 4 non-financial distress companies. Potential financial distress using the Springate S-Score method that in 2018 there were 11 companies experiencing financial distress and 4 non-financial distress companies. In 2019 there were 11 companies experiencing financial distress and 4 non-financial distress companies. In 2020 14 companies were experiencing financial distress, and 1 was in the non-financial distress category. In 2021 there are 15 companies experiencing financial distress and no companies in the non-financial distress category. This potential financial distress is a signal of self-quality that the company informs external parties which is useful in making future decisions.